Implementasi Penggunaan Metode At-Tartil dalam Pembelajaran BTQ di MI Thoriqussalam - Wahyudi, Ilham; Salahuddin, Rahmad (Universitas Batanghari Jambi, 2024)
The implementation of learning to read and write the Quran can be maximized with the support of competent teachers, adequate facilities, and effective methods. The At-Tartil method is considered suitable for enhancing students' abilities in reading and writing the Quran. The aim of this research is to understand the implementation in terms of planning, execution, and evaluation regarding the application of the At-Tartil method in Quranic learning at MI Thoriqussalam. This qualitative study utilizes observational and interview data, which are then analyzed descriptively. The findings of this research indicate that overcoming difficulties in reading the Quran for students at MIThariqussalam is designed and discussed collaboratively. The application of the At-Tartil method to address the challenges in reading the Quran by students at MI Thariqussalam is carried out through a modular system. The evaluation of the results of implementing the At-Tartil method to overcome difficulties in reading the Quran at MI Thariqussalam is conducted as a form of assessment. This evaluation aims to improve the students' Quran reading abilities and provides data as the basis for revising the At-Tartil method at the end of each year.Evaluation of the At-Tartil method at MI Thariqussalam generally involves oral tests as a form of assessment. Despite this, the At-Tartil method is considered to have been implemented effectively, with its main advantage lying in the simplicity of the language used in the materials delivered by instructors and learned by students.